Produccion En Banano Cavendish Con Desmane Falsa Mas Dos Y Falsa Mas Tres - Parrales, Yary Ruiz; Betancourt, Ricardo X. Chávez; Barbotó, Víctor Molina; Camposano, Cristina Maldonado; Arias, David Mayorga (European Scientific Journal, ESJ, 2016)
Producers have given importance only to the management of the plantation; however, only a little bit has been done to properly manage the bunch, the same that has affected the quality of the exportable fruit. In this research the trimming of bunches of Cavendish clone was made; the treatments were: False plus three, false plus two and witness (without trimming). The aim in this research was to: Determine whether the practice of hand pruning improves the presentation of the bunch, makes greater fruit and to obtain greater bunch / conversion box. Assess the economic effect of the treatments studied. Once this investigation was done, it was found that the bunch / box conversion increased, and the trimming managed to increase the length of the fingers on the lower hand, increased the weight hand, increased grade and were able to reduce the rejection rate and decline fruit. The results showed statistical differences for the length of fingers and grade, number of hands and weight of hands; however, it showed that it was no significant differences for weight on bunches and rachis. It is important to note that there is greater bunch / conversion box reaching 1.2 and 1.3 for False plus two and False plus three, respectively, while the witness was 0.9; this difference was due to rejection and decline fruit Because it was higher in the witness who did not reach the length or the degree required for export.